2018
DOI: 10.1080/02640414.2018.1483178
|View full text |Cite
|
Sign up to set email alerts
|

Cortical and trabecular bone analysis of professional dancers using 3D-DXA: a case–control study

Abstract: Given the lack of relevant data, the aim of this study was to examine femur cortical and trabecular bone in female and male professional ballet dancers. 40 professional ballet dancers and 40 sex- and age-matched non-exercising controls volunteered. Femoral bone density was scanned by dual-energy X-ray absorptiometry (DXA) scan. A 3D-DXA software was used to analyse trabecular and cortical bone. Anthropometry, maturation (Tanner staging), menstrual parameters (age at menarche and primary amenorrhea), energy ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…We found no significant changes in BMI percentile, percent body fat, or bone density from before to after the intervention. However, a longer duration of the intervention may be more likely to benefit both body composition and bone health (37, 38).…”
Section: Discussionmentioning
confidence: 99%
“…We found no significant changes in BMI percentile, percent body fat, or bone density from before to after the intervention. However, a longer duration of the intervention may be more likely to benefit both body composition and bone health (37, 38).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, another method for non-invasive bone structure assessment using DXA images called 3D-SHAPER was developed (21). 3D-SHAPER modeling provides a detailed proximal femur analysis including separate assessment of the cortical layer and trabecular macrostructure, which could potentially improve identification of those at elevated fracture risk (21,22,23,24). This methodology has not been evaluated in patients with acromegaly.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding this subject, a recent study performed in our laboratory in artistic swimmers has shown the importance of considering a complementary workout out of the water to improve femoral neck aBMD [30]. Moreover, a research performed on professional ballet dancers using 3D-DXA modelling revealed significantly higher aBMD, trabecular and cortical vBMD and cortical thickness compared to sedentary controls [31]. Artistic swimmers perform similar movements and have analogous aesthetic characteristics as ballet dancers except for the weight-bearing forces generated by the impacts with the floor, which could explain the higher bone density values found in ballet dancers.…”
Section: Accepted Manuscriptmentioning
confidence: 94%